The chemical ecology of defense in arthropods - Pasteels, Jacques M.; Grégoire, J. C.; Rahier, Martine (My University, 1983)
Oreina cacaliae (Coleoptera, Chrysomelidae) produces in its elytral and pronotal defensive secretion seneciphylline N-oxide together with small amounts of another pyrrolizidine alkaloid tentatively identified as senecionine N-oxide. This is a strong departure from the chemical composition of the defensive secretions in related species, characterized by complex mixtures of cardenolides, synthesized by the beetles from cholesterol. It is suggested that O. cacaliae sequesters the alkaloids from its host-plant, Adenostyles leucophylla. Other specimens of O. cacaliae from far distant populations feeding on Senecio nemorensis, Petasites paradoxus or P. album also produced pyrrolizidine alkaloids, but not O. speciosissima feeding on the same food plants and producing cardenolides. In addition to pyrrolizidine alkaloids, O. cacaliae secretes ethanolamine, which is also found in all the cardenolide-producing species.
Keywords: pyrrolizidine alkaloids; seneciphylline N-oxide; Oreina; Chrysomelidae; leaf beetles; defensive secretion; sequestration; host-plant influence; Adenostyles leucophylla